Colorectal and anal cancer in HIV/AIDS patients: a comprehensive review. Issue 4 (April 2014) - Kan, Manstein; Wong, Patrick Ho Pun; Press, Natasha; Wiseman, Sam M
<x xml:space="preserve">Abstract</x> Highly active antiretroviral therapy (HAART) has significantly altered the epidemiology of cancer that is diagnosed in individuals who are infected with the human immunodeficiency virus (HIV). Studies have shown a dramatic decrease in the incidence of and mortality from AIDS-related malignancies (primarily Kaposi sarcoma and non-Hodgkin's lymphoma), while the incidence of and mortality from non-AIDS defining malignancies is on the rise. While the risk of colorectal cancer (CRC) in HIV-infected individuals is controversial and has received limited study, there has been accumulating evidence that suggests an increased risk of developing anal cancer (AC) during the HAART era. This article reviews the current literature reporting on CRC and AC in the HIV-infected population, with a specific on cancer: incidence, screening, clinical characteristics, and treatment outcomes.